Central corneal thickness measured with three optical devices and ultrasound pachometry - González-Pérez, Javier (2011)
Purpose: To evaluate the reliability of three noninvasive pachometry methods against the ultrasound pachometer considered the gold standard. Methods: Central corneal thickness (CCT) was measured using a Paxis ultrasound (US) pachometer, Orbscan II, Pentacam, and Topcon SP-3000 specular microscope in 22 right eyes of 22 healthy adults (7 men, 15 women). Three repeated measures were obtained and then compared to obtain the repeatability of each instrument and the agreement between pachometers. Results: Pentacam is the optical system that renders values of CCT closer to those obtained with US pachometry. Conversely, a specular microscope shows a poorer agreement with US measures, and differences depend on the thickness being measured. The Orbscan system shows a consistent trend toward underestimation of CCT compared with US and Pentacam irrespective of the value measured. Conclusion: Different optical methods used to measure CCT showed significantly different results compared with US pachometry except for the Pentacam system. Clinicians should take into account the fact that specular microscopy might either underestimate or overestimate values of CCT, whereas Orbscan systematically overestimates CCT compared with US and Pentacam.